POSTFEMINISM CONCEPT IN LUX INDONESIA “LUX BERANI CANTIK 30” ADVERTISEMENT: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS - Hanifah, Owyana Nur; Kurniawan, Muhammad Hafiz; Farida, Hana; Atmantika, Zanuwar Hakim (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
Advertisement does not only promote products but also conveys a message behind the promotion. One of the current trending concepts is femvertising. The initial purpose of femvertising is to fill the concept of advertising that uses pro-female talent, words, and images to empower women and girls. As a result, advertising has attracted more consumers and evolved into a movement aimed at selling more items to women rather than a genuine subversion and changing gender stereotypes. Lux is also one of the brands indicated to use the advertising concept, as in its advertisement "LUX Berani Cantik 30" (LUX Dare to be Beautiful 30). Following the advertising concept, this research explores how LUX represents feminist elements in its advertisement using the Multimodal Critical Discourse Analysis (MCDA) theory by Machin and Mayr (2012) and a descriptive qualitative approach. The findings demonstrate that lexical and visual multi modal aspects indicate the interrelation of meaning between interconnected aspects. The resulting meaning in Lux ads reflects the interpretation of feminine women who dare to express their beauty in front of the public.